2019
DOI: 10.3390/healthcare7040113
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Primary Healthcare Students and Their Mentors’ Awareness of Mentorship and Clinical Governance as Part of a Local Continuing Professional Development (CPD) Program: Findings of a Quantitative Survey

Abstract: : Introduction: Research by Snowden [1] and Elwood et al. [2] exploring the benefits of mentoring and the place of clinical governance in enhancing care delivery illustrated an unexplored synonymous relationship between mentors and mentees (students at undergraduate and postgraduate levels) and its potential impact on patient safety and quality of care. The significance of the research was in recognizing the importance the role of the mentor can play in raising awareness of patient safety and clinical governan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Building upon this, despite the paucity of mentoring literature in the field of social enterprise (Thomaz and Catalão-Lopes, 2019), Oberoi et al (2020a) and Oberoi et al (2020b) illustrate its relevance to social enterprise organizations and the development of social entrepreneurs. The skills identified previously by McSherry and Snowden (2019) clearly resonate with the findings from the authors' experience on this project.…”
Section: Best Practise In Global Social Enterprisesupporting
confidence: 76%
See 1 more Smart Citation
“…Building upon this, despite the paucity of mentoring literature in the field of social enterprise (Thomaz and Catalão-Lopes, 2019), Oberoi et al (2020a) and Oberoi et al (2020b) illustrate its relevance to social enterprise organizations and the development of social entrepreneurs. The skills identified previously by McSherry and Snowden (2019) clearly resonate with the findings from the authors' experience on this project.…”
Section: Best Practise In Global Social Enterprisesupporting
confidence: 76%
“…(Snowden, 2019, p. 123) Nonetheless, experiences on this project have demonstrated that the transfer of experience, knowledge and skills of the mentor is a challenging and transformative process that requires key skills, qualities and abilities. McSherry and Snowden (2019) suggest that there are four key attributes of the mentor to ensure effective transference; these include the ability to teach, explain, prioritize and develop interpersonal skills, the ability to provide constructive and critical feedback based upon both negative and positive experiences, a critical awareness of standards that are commensurate with excellence, and the ability to develop and construct awareness of politics that influence practice.…”
Section: Best Practise In Global Social Enterprisementioning
confidence: 99%
“…After the data collection was completed, the authors of the research implemented a thematic analysis strategy for all of the data that was collected (Guest, et al, 2012). The work that is presented in this paper builds on previous published articles by the authors (please see : Oberoi, et al, 2020;2019;2018).…”
Section: Research Approachmentioning
confidence: 97%
“…Clearly, as Snowden and Hardy assert, "mentoring enables the mentee "to make best use of the resources available by accessing the 'inside knowledge' that the mentor possesses" (2012, p. 90). Mentoring, as a strategy to promote success, is acknowledged in a variety of different contexts; for example, business, medicine, nursing, dentistry, law, and education all recognize the importance that the mentoring role has on personal development and the development of practice (McSherry & Snowden, 2019). Furthermore, the importance of the mentor in the development of social enterprise and the personal development of social entrepreneurs is emphasized by organizations such as Social Enterprise UK, The British Council and the School for Social Entrepreneurs.…”
Section: Mentoring Social Enterprise In Higher Educationmentioning
confidence: 99%
“…However, to facilitate the transfer of experience, knowledge and skills this in itself is a challenging and transformative process that requires key skills, qualities and abilities. McSherry and Snowden (2019) highlight these when exploring mentorship within health and social care.…”
Section: Mentoringmentioning
confidence: 99%